LİPİT İÇERENMİKRO ALGLERİN (CHLORELLA EMERSONİİ VE BOTRYOCOCCUS BRAUNİİ) ATIKSULARIN İLERİ ARITIMINDA KULLANIMI - İLHAN, ESRA (Fırat Üniveristesi, 2015)
The Use in of Advanced Treatment of Wastwewater of Lipids Containing Microalgae (Chlorella emersonii and Botryococcus braunii) This work aims to analyze the possibility of growing lipid containing microalgae Chlorella emersonii and Botryococcus braunii'in wastewater as a potential candidate for biodiesel production. In this study, the growth performances of C.emersonii and B. Braunii were determined in the laboratory with synthetic wastewater. Nutrient removal efficiencies of microalgae were also investigated. Each trial was done for a period of 13 days in the laboratory at average 25 0C. Under these conditions, results for synthetic wastewater revealed average lipid contents of C.emersonii ve B. braunii 37-43 % and 31-34 % of dry-weight (dwt) biomass, respectively. The results showed that by the end of a 13-day continuous culture, B.braunii could remove ammonia nitrogen, total phosphorus, and total organic carbon (TOC) by % 81-97, % 94-99 and % 60-83, respectively from synthetic wastewater and the results also showed, C. emersonii could remove ammonia nitrogen, total phosphorus, and total organic carbon (TOC) by 82-93 %, 93-98% and 62-81 % respectively from synthetic wastewater. According to our findings, B.braunii and C. emersonii contains significant amounts of lipids for biodiesel production. At the same time high nutrient removal from wastewater is provided. For this reasons, these species both for the tertiary treatment of wastewater and for biodiesel production can be used. Key words: Wastewater, Microalgae, Biodiesel, Tertiary Treatment, Nutrient Removal, Lipid Production.

Bu çalışma biyodizel üretimi için potansiyel bir aday olarak atıksularda lipit içeren Chlorella emersonii ve Botryococcus braunii' in mümkün olan gelişmelerini analiz etmeyi amaçlamaktadır. Aynı zamanda mikroalglerin bitki besin maddeleri giderim verimlilikleri de araştırıldı. Her bir deney laboratuvarda ortalama 25 0C sıcaklıkta 13 günlük periyotlar halinde yapıldı. Bu şartlar altında sentetik atık sular için C.emersonii ve B. braunii'nin lipit içeriklerinin biyomas kuru ağırlığı başına sırasıyla, % 36-52, % 24-36 olduğu ortaya konuldu. Sonuçlar 13 günlük sürekli kültür çalışmaları ile sentetik atıksularla yapılan çalışmalarda B.braunii' nin amonyum azotu, toplam fosfor ve toplam organik karbonu sırasıyla % 81-97, % 74-99 ve % 67-84 giderildiğini ve C. emersonii için amonyum azotu, toplam fosfor ve toplam organik karbonun sırasıyla % 82-94, % 81-96 ve % 74-83 uzaklaştırılabileceğini gösterdi. Bulgularımıza göre B. braunii ve C. emersonii biyodizel üretimi için önemli miktarlarda lipit içermektedir. Aynı zamanda atık sulardan yüksek besin maddesi uzaklaştırma yeteneğine sahiptir. Bu sebeplerden dolayı bu türler hem atık suların üçüncül arıtımı için hem de biyodizel üretimi için kullanılabilirler. Anahtar Kelimeler: Atık Su, Mikroalg, Biyodizel, Üçüncül Arıtım, Bitki Besin Maddeleri Giderimi, Lipit Üretimi
The use in of advanced treatment of wastwewater of lipids containing microalgae (Chlorella emersonii and Botryococcus braunii)
Keywords: Çevre Mühendisliği